Evaluation of Pant-Winged Sub-soiler in Relation to Soil Properties and Maize Crop Response - Kumar, Arun; Thakur, T. C.; Gautam, R. C. (Journal of Agricultural Engineering, 2014)
A winged sub-soiler with shallow leading tines was developed and its performance was compared with conventional curved leg sub-soiler available in India. An experiment was conducted in sandy loam soil in kharif season using RBD with 3 treatments viz. T1: Harrow x 3 + Planker x1 (Control), T2: Winged sub-soiler with shallow leading tines + Harrow x 1 + Planker x1 and T3: Conventional curved leg sub-soiler + Harrow x 1 + Planker x1 having 6 replications each of 3 x 25 m plot size. Observations on crop growth parameters at different stages, yield contributing characters and yield were noted. Results showed 16.5 % increase in maize yield (at 15% m.c) by Pant winged sub-soiler with shallow leading tines over conventional tillage and 12.2% increase over conventional sub-soiler.